Effect of 3 to 5 years of scheduled CEA and CT follow-up to detect recurrence of colorectal cancer The FACS Randomized Clinical Trial - Primrose, John N.; Perera, Rafael; Gray, Alistair; Rose, Peter; Fuller, Alice; Corkhill, Andrea; George, Steve; Mant, David (American Medical Association, 2014)
IMPORTANCE Intensive follow-up after surgery for colorectal cancer is common practice but is based on limited evidence. OBJECTIVE To assess the effect of scheduled blood measurement of carcinoembryonic antigen (CEA) and computed tomography (CT) as follow-up to detect recurrent colorectal cancer treatable with curative intent. DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial in 39 National Health Service hospitals in the United Kingdom; 1202 eligible participants were recruited between January 2003 and August 2009 who had undergone curative surgery for primary colorectal cancer, including adjuvant treatment if indicated, with no evidence of residual disease on investigation. INTERVENTIONS Participants were randomly assigned to 1 of 4 groups: CEA only (n = 300), CT only (n = 299), CEA+CT (n = 302), or minimum follow-up (n = 301). Blood CEA was measured every 3 months for 2 years, then every 6 months for 3 years; CT scans of the chest, abdomen, and pelvis were performed every 6 months for 2 years, then annually for 3 years; and the minimum follow-up group received follow-up if symptoms occurred. MAIN OUTCOMES AND MEASURES The primary outcome was surgical treatment of recurrence with curative intent; secondary outcomes were mortality (total and colorectal cancer), time to detection of recurrence, and survival after treatment of recurrence with curative intent. RESULTS After a mean 4.4 (SD, 0.8) years of observation, cancer recurrence was detected in 199 participants (16.6%; 95% CI, 14.5%-18.7%) overall; 71 of 1202 participants (5.9%; 95% CI, 4.6%-7.2%) were treated for recurrence with curative intent, with little difference according to Dukes staging (stage A, 5.1% [13/254]; stage B, 6.1% [34/553]; stage C, 6.2% [22/354]). Surgical treatment of recurrence with curative intent was 2.3% (7/301) in the minimum follow-up group, 6.7% (20/300) in the CEA group, 8% (24/299) in the CT group, and 6.6% (20/302) in the CEA+CT group. Compared with minimum follow-up, the absolute difference in the percentage of patients treated with curative intent in the CEA group was 4.4% (95% CI, 1.0%-7.9%; adjusted odds ratio [OR], 3.00; 95% CI, 1.23-7.33), in the CT group was 5.7% (95% CI, 2.2%-9.5%; adjusted OR, 3.63; 95% CI, 1.51-8.69), and in the CEA+CT group was 4.3% (95% CI, 1.0%-7.9%; adjusted OR, 3.10; 95% CI, 1.10-8.71). The number of deaths was not significantly different in the combined intensive monitoring groups (CEA, CT, and CEA+CT; 18.2% [164/901]) vs the minimum follow-up group (15.9% [48/301]; difference, 2.3%; 95% CI, −2.6% to 7.1%). CONCLUSIONS AND RELEVANCE Among patients who had undergone curative surgery for primary colorectal cancer, intensive imaging or CEA screening each provided an increased rate of surgical treatment of recurrence with curative intent compared with minimal follow-up; there was no advantage in combining CEA and CT. If there is a survival advantage to any strategy, it is likely to be small. TRIAL REGISTRATION isrctn.org Identifier: 41458548